Islamic Republic Of Mauritania : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2003)
This Selected Issues paper covers three topics of particular relevance to Mauritania: export competitiveness and exchange rate policy, the monetary policy framework, and the transfer of government deposits from commercial banks to the central bank. The paper reports on the recent economic developments over 1999-2001. It describes a stable macroeconomic environment with robust growth, low inflation, manageable current account deficits, and a comfortable level of gross foreign reserves. The paper also looks at the issue of export competitiveness and exchange rate policy.